Analysis of Service Quality on Satisfaction Customers at the Salatiga City Type A Boarding Terminal - Dava Ananda; Sulistyowati Sulistyowati; Andar Sri Sumantri (Digital Innovation : International Journal of Management, 2025)
This research aims to determine the analysis of service quality on customer satisfaction at the Tingkir Type A Terminal, Salatiga City. In this research, the objects taken were service users at the Tingkir Terminal. Data sources include primary and secondary data. The sample in this study was 100 service user respondents at Tingkir Terminal. Data collection was carried out using observation methods, literature studies, interviews, documentation and questionnaires. The data analysis technique is a multiple linear regression technique which is first tested through a questionnaire test (validity and reliability) and classical assumption tests (autocorrelation, heteroscedasticity, multicollinearity, normality). The results of the analysis using the statistical tools of the SPSS V.26 program obtained a multiple linear regression equation: Y = 2,637 + 0,170.X1 + 0,203.X2 + 0,180.X3 + 0,179.X4 + 0,171.X5 + μ. The results of the multiple linear regression equation show that the Tangible Variable (X1) has a tcount of 0.170 and a ttable of 1.66105, so H0 is rejected and Ha is accepted. The Reability variable (X2) has a tcount of 0.203 and a ttable of 1.66105, so H0 is rejected and Ha is accepted. The Responsive Variable (X3) has a tcount of 0.180 and a ttable of 1.66105, so H0 is rejected and Ha is accepted. The variable Emphaty (X4) has a tcount of 0.179 and a ttable of 1.66105, so H0 is rejected and Ha is accepted. The Assurance variable (X5) has a tcount of 0.171 and a ttable of 1.66105, so H0 is rejected and Ha is accepted. Based on the results of the study, conclusions can be drawn from multiple linear regression analysis and the distribution of respondents' answers regarding independent variables (Tangible, Reability, Responsive, Emphaty, Assurance) has an influence on the dependent variable (Customer Satisfaction).